Reconfiguring Gender Through Digital Narratives: Multiliteracies and Social Justice in Additional Languages Teacher Education - Margarida Castellano Sanz; Agustín Reyes-Torres (Asparkía)
This article explores the integration of multimodal narratives and feminist perspectives in additional language education to promote social justice. Drawing on the Pedagogy of Multiliteracies, which emphasizes the need to engage with diverse modes of meaning construction, the text discusses how digital resources contribute to challenge traditional gender roles and foster inclusive learning environments. Through a theoretical framework grounded in the dimensions of literacy, learning by design, and social justice, and under a feminist lens, we examine the transformative potential of incorporating gender discussions into language education. Additionally, the role of multimodal texts in expanding students’ multiliteracies is explored, offering a practical learning path to promoting gender equity and empowering future teachers as agents of change.